A Genome-Scale CRISPR Knock-Out Screen Identifies MicroRNA-5197-5p as a Promising Radiosensitive Biomarker in Colorectal Cancer - Yu, Shijun; Li, Li; Fan, Kailing; Li, Yandong; Gao, Yong (Frontiers in Oncology, 2021)
Radioresistance is one of the main reasons causing unsatisfactory curative effects of ionizing radiation (IR) against colorectal cancer (CRC). However, its underlying mechanisms remain unclear yet. In the present study, we applied a genome-scale CRISPR knockout screen in combination of NGS sequencing upon CRC cell lines to explore regulatory factors involved radioresistance of CRC, and 3 candidate genes were identified. Cytotoxicity of IR was determined by Cell Counting Kit-8 (CCK-8) assay, colony formation assay and apoptosis assay, and microRNA-5197-5p (miR-5197) was found to significantly enhance the cytotoxicity of IR to CRC cells. By further mechanistic investigation, we demonstrated that miR-5197 directly targeted CDK6 and inhibited its expression in RKO cells, which induced cell cycle arrest at G1/S phase and inhibited cell division, thereby radiosensitivity was enhanced by miR-5197. Our findings revealed that miR-5197 might be a critical factor regulating CRC cell radiosensitivity and provided novel insights into the development of therapeutic strategies for CRC patients who are resistant to IR.